2011
DOI: 10.1038/nature10106
|View full text |Cite
|
Sign up to set email alerts
|

Direct reprogramming of somatic cells is promoted by maternal transcription factor Glis1

Abstract: Induced pluripotent stem cells (iPSCs) are generated from somatic cells by the transgenic expression of three transcription factors collectively called OSK: Oct3/4 (also called Pou5f1), Sox2 and Klf4. However, the conversion to iPSCs is inefficient. The proto-oncogene Myc enhances the efficiency of iPSC generation by OSK but it also increases the tumorigenicity of the resulting iPSCs. Here we show that the Gli-like transcription factor Glis1 (Glis family zinc finger 1) markedly enhances the generation of iPSCs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
287
4
4

Year Published

2011
2011
2015
2015

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 352 publications
(302 citation statements)
references
References 26 publications
2
287
4
4
Order By: Relevance
“…All of these aberrations likely appear because of the imperfection of the reprogramming procedure, as illustrated by the low efficiency of reprogramming. Efforts have to be made to improve culture conditions and factors [79] available to the cells during reprogramming, which could lower the number of stochastic steps the cell needs to breach in order to achieve pluripotency. This would likely increase the ratio of true versus bad quality iPSC colonies and lower the aberrations present in the cells.…”
Section: Resultsmentioning
confidence: 99%
“…All of these aberrations likely appear because of the imperfection of the reprogramming procedure, as illustrated by the low efficiency of reprogramming. Efforts have to be made to improve culture conditions and factors [79] available to the cells during reprogramming, which could lower the number of stochastic steps the cell needs to breach in order to achieve pluripotency. This would likely increase the ratio of true versus bad quality iPSC colonies and lower the aberrations present in the cells.…”
Section: Resultsmentioning
confidence: 99%
“…It is enriched in unfertilized eggs and zygotes, and could replace cMyc to produce iPSCs from adult cells with a higher efficiency and decreased tumorigenicity (Maekawa et al, 2011). Mechanistic studies revealed that the Glis1 protein interacts with Oct4, Sox2, and Klf4.…”
Section: Molecular Mechanism Of Reprogramming To Pluripotency the Funmentioning
confidence: 99%
“…The gene targets of Glis1 include several Wnt ligands, Lin28a (a homologue of Lin28), Nanog, Mycn, Mycl1, and Foxa2. They propose that Glis1 facilitates iPSC formation by activating multiple pro-reprogramming pathways (Maekawa et al, 2011).…”
Section: Molecular Mechanism Of Reprogramming To Pluripotency the Funmentioning
confidence: 99%
“…Maekawa et al found that Glis1 markedly enhances the generation of iPSCs from both mouse and human fibroblasts when it is expressed together with OSK. Even more importantly, this four transcription factors generated mouse iPSCs can form germline-competent chimaeras (Maekawa et al, 2011). To undertake further research of the mechanism, they found Glis1 promotes multiple pro-reprogramming pathways, including Myc, Nanog, Lin28, Wnt, Essrb and the mesenchymal-epithelial transition, to promote the direct reprogramming of somatic cells during iPSC generation.…”
Section: Improving the Quality Of Ips Cellsmentioning
confidence: 99%
“…Tbx3 is necessary for safeguarding the pluripotency of mouse ES cells, as its knockdown elicits © Higher Education Press and Springer-Verlag Berlin Heidelberg 2012 differentiation (Ivanova et al, 2006). It appears to have pleiotrophic roles, as it is also required for mammary bud development and limb development (Carlson et al, 2002;Esteban et al, 2009;Graf et al, 2009;Maekawa et al, 2011). Furthermore, overexpression of Tbx3 in conjunction with Myc or oncogenic Ras leads to the efficient oncogenic transformation of mouse fibroblasts; it appears that Tbx3's role in oncogenic cooperation is to inhibit the induction of p53 and p19 ARF that is typically triggered by Myc and Ras (Carlson et al, 2002).…”
Section: Improving the Quality Of Ips Cellsmentioning
confidence: 99%